Sedimentology and geochemistry of Campanian–Maastrichtian sandstones of Enagi Formation, Bida Basin, Nigeria - James Adejimi Adeoye; Ishaq Yusuf; Nuhu George Obaje; Abubakar Alhaji Usman; Ugochukwu Charles Okoro (Discover Geoscience)
Abstract The provenance, paleoenvironments, and mineralogical studies of the sandstones of the Enagi Formation at Gulu and Kandi in the Bida Basin were investigated for preliminary reservoir quality assessment. The average values of quartz, feldspar, and rock fragments of 76.2%, 8.7%, and 15.1% at Gulu and 59.3%, 24.6%, and 16.2% at Kandi suggest they are litharenitic and arkosic sandstones respectively. The grain size bivariate plots indicate that the Kandi and Gulu sandstones were deposited mainly within the fluvial system with low contribution from the marine and tidal environments. The moderately sorted, medium to very coarse-grained sandstone beds suggest typical braided and channel deposits while the few poorly sorted ones represent floodplain deposits. Al2O3/ TiO2, Zr/TiO2, and paleo-tectonics discriminant-function multi-dimensional diagram suggest a dominant felsic igneous origin and continental rift environment for all the samples. The sandstone beds with poorly sorted, fine-grained, immature texture and mineralogy classified as arkosic will likely have less reservoir or aquifer potential. Those beds with moderately sorted, medium to coarse-grained sub-mature texture and mineralogy classified as litharenitic represent the lithofacies with the potential to develop or maintain better porosity and permeability for a good reservoir or aquifer even at the deep subsurface. This study for the first time identified favorable geological indices for a Campanian–Maastrichtian sandstone reservoir within the Enagi Formation of the northern Bida Basin. The result of this study will further encourage exploration of the Campanian–Maastrichtian lithofacies in the West African Cretaceous rift basins for prospective underground water and hydrocarbon reservoirs.